Photoactive Hexaazaphenalene‐based Coordination Network as a Two‐Pathway Photosensitizer for Oxidation of Alkanes. Issue 3 (18th January 2023) - Deekamwong, Krittanun; Wada, Yuki; Zhu, Yiying; Usov, Pavel M; Tagami, Yu; Ohtsu, Hiroyoshi; Kawano, Masaki
Abstract: A tris(4‐pyridyl) hexaazaphenalenyl anion (TPHAP − ) exhibited both energy and charge transfer processes to oxygen molecules under UV irradiation resulting in the production of reactive oxygen species (ROSs). The existence of ROSs was confirmed by spectroscopic characterization and photooxidation of a standard compound selective for the singlet oxygen, 1, 5‐dihydroxynaphthalene (1, 5‐DHN). In addition, a porous coordination network (PCN) consisting of TPHAP −, cadmium ions and fumarate co‐ligand was synthesized and used as a heterogeneous photosensitizer capable of ROSs generation. To take advantage of this ability, photooxidation of various saturated hydrocarbons including cyclohexane, cyclooctane and n ‐octane was investigated. TPHAP‐based PCN demonstrated excellent photosensitizing ability achieving more than a hundred times higher turnover frequency than other reported coordination networks based on photoactive ligands. Abstract : Photosensitizer for Oxidation of Alkanes : A porous coordination network consisting of tris(4‐pyridyl) hexaazaphenalenyl anion, as a new photosensitizer motif, cadmium ions and fumarate co‐ligand was synthesized and tested as a heterogeneous photocatalyst capable of dual‐pathway reactive oxygen species generation under UV light in the air. It was successfully used for oxidation of alkanes, including cyclohexane, cyclooctane and n ‐octane.